An experiment with the minor geographies of major cities: Infrastructural relations among the fragments. (June 2022) - R, Niranjana
Research on urban water infrastructures has seldom reached across the Global North-South divide owing to their apparent developmental incommensurability. Yet, the universalising tendencies of urban theory has meant that cities of the Global South are often deemed to have 'fragmented' infrastructures or incomplete circulations in implicit comparison to the northern infrastructural ideal. So, in order to truly 'world' the study of infrastructures and cities, it is important to go beyond these dominant paradigms and attend to how infrastructures actually work and what socio-technical implications they have in cities of the Global South and North. Building on these provocations, this paper places the water infrastructures of two 'most different cities'– Chennai, India and London, UK – alongside each other in 'experimental comparison', where the aim is not to arrive at paradigmatic urban theory but to highlight heterogeneity and excavate themes for further critical thinking on each case. This paper will delineate the dialogic and reflexive method of research and analysis adopted, tracing how it led to the practice of 'minor theory', which focuses on processes that do not find expression in dominant universalising analyses. Here, minor theory is mobilised towards challenging dominant or major constructs about each city and across cities, while amplifying urban multiplicities and enabling a deeper engagement with infrastructure making in the Global South and North, thus expanding urban studies' toolbox of critical thinking.